Language Learner’s Use of a Bilingual Dictionary: A Comparative Study of Dictionary Use and Needs - Mdee, James Salehe (Lexikos, 1997)
This paper compares and contrasts dictionary use and needs of language learners at the University of York in the United Kingdom and at the University of Dar es Salaam in Tanzania. Five aspects are discussed in this study viz. dictionaries used, instructions and guidance on dictionary use, the functions for which students use a dictionary, information categories sought or lacking, metalanguage in the dictionaries and how it has been used to explicate the information categories. These five aspects are discussed in relation to the observations made by the subjects as reflected in the data collected. From the data analysis are made some generalizations on how the language students of the two universities use their dictionaries and the lexicographical needs of the language learners in general and of each group in particular. It is concluded that language learners do not look up the same information in a dictionary because each has specific language problems.